Pengaruh Beban Kerja dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan Kantor Pos Cabang Utama Surabaya 6000 - Siti Nur Munazilah; Endang Iryanti (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine whether workload and work discipline affect job satisfaction. The research method used is saturated sampling methodology consisting of 36 permanent employees of the marketing and service division using a questionnaire. The results of this study indicate that workload can contribute to increasing employee job satisfaction, and work discipline can contribute to increasing employee job satisfaction. Keywords: Workload, Work Discipline, Job satisfaction